APPROACHES TO ONLINE LEARNING - FROM IMITATION TO INNOVATION (Heritage, 2023)
Online learning has become an integral part of the educational environment, especially in higher education. Although the practice is not yet widespread or systematized, there seems to be an increasing number of institutions and individuals embracing this innovation. This increase is not limited to the developed world; the teaching staff in developing countries are equally enthusiastic about mediated learning for various reasons, including expanding access and providing flexibility to the population seeking education and continuous training. The ubiquity and multitude of ways and tools for communication among people are the most notable characteristics of network-based culture and economy. Institutions that previously relied on students gathering in classrooms can now offer their study programs online. The frameworks of implementation of digital techology range from those that imitate traditional classroom patterns to models that fully leverage the potential of digital technology to create an authentic learning environment. The paper presents five models of online learning, from those that use technology as a support to the traditional approach, such as the flipped classroom model and the virtual classroom model. It then moves on to the blended learning model, which sits in the middle of the continuum between imitation and innovation, representing a fundamental change in the approach to education. Finally, the paper introduces the model of collaborative online learning and the model of connectivist learning, implemented in the form of massive open online courses, which represent a disruptive innovation that threatens to destabilize the world of formal education.
Keywords: online learning, collaborative online learning, massive open online courses, flipped classroom model, blended learning, higher education, digital technology